EFEK PERISTIWA POLITIK TERHADAP KINERJA PASAR MODAL INDONESIA (Even Study Pada Vonis Yang Diberikan Kepada Basuki Tjahaja Purnama) (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis study aims to determine differences in Abnormal Return before and after theverdict of Ahok was set on May 9, 2017. The test equipment used was PairedSamples t-test. Based on the results of an analysis of the event study (event study)on the verdict of Ahok shows that the activity in the capital market of stock priceshas a high market capitalization, namely by calculating the value of t before andafter the verdict of Ahok on May 9, 2017. The results of this study indicate thatthere is a significant abnormal return that can be enjoyed by investors with t<0.05. This shows that there are differences before and after the event. So it canbe concluded that the event of the adoption of Ahok's verdict on May 9, 2017using the abnormal return indicator contains negative information, so investors inthe capital market react).Keyword: Abnormal Return, Vonis Ahok.